Rwanda : Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Request for Waiver of Nonobservance of Performance Criterion, and Modification of Performance Criteria; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Rwanda. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
The Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility of Rwanda explains macroeconomic challenges. Indicative limits on domestic debt have been established. If these limits are exceeded or inflation is rekindled, the domestic component of fiscal spending must be released more gradually. On the structural side, the focus remains on public financial management (PFM) and the financial sector. The authorities' financial sector development plan is a sound basis for building long-term financial markets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet